ANALYSIS OF CAPITAL MARKET REACTION ON COMPANIES AFFECTED BY THE BOYCOTT, DIVESTMENT, AND SANCTIONS (BDS) MOVEMENT - Riafajri Mitayaningtyas; Adam Zakaria; Hafifah Nasution (Publikasi Inspirasi Indonesia, 2025)
This study aims to determine the response of the Indonesian capital market to global events, particularly the BDS movement against Israeli-affiliated products. The research method used in this study is an event study, comparing stock index, stock prices, abnormal returns, and trading volume activity 10 days before and after the event. The sample was selected using a total sampling technique from 8 companies on the boycott list. The data used is secondary data published by the Indonesia Stock Exchange (IDX). The statistical test technique used is the Wilcoxon Signed Rank Test. The results of this study indicate that there are no differences in stock index, stock prices, abnormal returns, and trading volume activity due to the BDS movement.